The Influence of Profitability on the Aggressiveness of Intercompany Transaction Tax as an Intervening Variable - Prasetia, Angga; M Anwar Masruri; Verni Asvariwangi; Rasiman; Ayu Lestari (Universitas Ibn Khaldun Bogor, 2024)
This study aims to analyze the impact of benefits on tax impulsiveness by making intercompany transactions as mediation. The object of this study is company records on the stock trade in Indonesia during 2020 - 2023, with 129 companies. The sampling strategy in this study was purposive sampling testing. The collected data were analyzed using descriptive analysis and statistical analysis techniques, using the WarpPLS 6.0 program. The results showed that profitability affected tax impulsiveness, profitability affected intercompany transactions, whereas intercompany transactions did not affect tax aggressiveness, while profitability towards tax aggressiveness through intercompany transactions resulted in no reconciliation. It is mentioned for further study to boost the number of defendants, the sample of companies studied, and their respective indicators.